Inhibition of sweet chemosensory receptors alters insulin responses during glucose ingestion in healthy adults: a randomized crossover interventional study. Issue 4 (1st March 2017) - Karimian Azari, Elnaz; Smith, Kathleen R; Yi, Fanchao; Osborne, Timothy F; Bizzotto, Roberto; Mari, Andrea; Pratley, Richard E; Kyriazis, George A
ABSTRACT: Background: Glucose is a natural ligand for sweet taste receptors (STRs) that are expressed on the tongue and in the gastrointestinal tract. Whether STRs directly contribute to the regulation of glucose homeostasis in response to glucose ingestion is unclear. Objective: We sought to determine the metabolic effects of the pharmacologic inhibition of STRs in response to an oral glucose load in healthy lean participants. Design: Ten healthy lean participants with a body mass index (in kg/m 2 ) of 22.4 ± 0.8 were subjected to an oral-glucose-tolerance test (OGTT) on 4 separate days with the use of a randomized crossover design. Ten minutes before the 75-g OGTT, participants consumed a preload solution of either 300 parts per million (ppm) saccharin or water with or without the addition of 500 ppm lactisole, a human-specific inhibitor of STRs. When present, lactisole was included in both the preload and OGTT solutions. We assessed plasma responses of glucose, insulin, C-peptide, glucagon, glucagon-like peptides 1 and 2, gastric inhibitory peptide, acetaminophen, and 3- O -methylglucose. With the use of mathematical modeling, we estimated gastric emptying, glucose absorption, β-cell function, insulin sensitivity and clearance, and the portal insulin:glucagon ratio. Results: The addition of lactisole to the OGTT caused increases in the plasma responses of insulin ( P = 0.012), C-peptide ( P = 0.004), and the insulin secretory rate ( P = 0.020) compared with the control OGTT. The addition of lactisole also caused a slight reduction in the insulin sensitivity index independent of prior saccharin consumption ( P < 0.025). The ingestion of saccharin before the OGTT did not alter any of the measured variables but eliminated the effects of lactisole on the OGTT. Conclusion: The pharmacologic inhibition of STRs in the gastrointestinal tract alters insulin responses during an oral glucose challenge in lean healthy participants. This trial was registered at clinicaltrials.gov as NCT02835859.